Oxidative stress and inflammation caused by n-Hexyl salicylate in mouse skin: the effectiveness of flavonoids - Nada Orsolic; Vedran Balta; Dyana Odeh; Maja Mataković; Jadranka Skurić (International Journal of Phytomedicine, 2017)
Reactive oxygen species (ROS) play a role in a numbered of degenerative conditions including psoriasis. Psoriasis is a chronic inflammatory disease who’s the etiopathogenesis is not yet completely understood, and therefore there is no standardized therapeutical approach. Flavonoids, recognized as potent antioxidants, are multifunctional molecules that can act as anti-inflammatory and antiproliferative agents through the modulation of multiple signaling pathways. The present study was designed to investigate the protective role of flavonoids [quercetin, chrysin, curcumin or Epigallocatechin 3-gallate (EGCG)] against n-Hexyl salicylate (HXS)-induced oxidative stress and inflammation in skin. Anti-oxidative and anti-inflammatory effect of flavonoids is quantified by histopathological assessment of skin, measuring the levels of lipid peroxidation and glutathione (GSH) in the skin, total number of inflammatory cells in peritoneal cavity, macrophage spreading index, and hematological and biochemical parameters. Topically applied of n-Hexyl salicylate caused significant increase in lipid peroxidation and decrease in GSH, which is accompanied by an increase total number of inflammatory cells in skin and peritoneal cavity, functional activity of macrophages, and enzymatic activity of ALP and AST. In contrast, topically applied 5 % preparation of flavonoids (quercetin, chrysin, curcumin or EGCG) with HXS effectively prevented these alterations and maintained the antioxidant status. The results suggest that flavonoid preparations can serve as a potent antioxidant and anti-inflammatory agents in psoriatic-like skin lesions, without toxic effects.